Cardiovascular risk factors and lifetime risk estimation in HIV-infected patients under antiretroviral treatment in Spain. Issue 2 (April 2015) - Estrada, Vicente; Bernardino, José Ignacio; Masiá, Mar; Iribarren, José Antonio; Ortega, Alejandra; Lozano, Fernando; Miralles, Celia; Olalla, Julián; Santos, Jesús; Elías, María Jesús Pérez; Domingo, Pere; Cruz, Arturo Fernández
Abstract : Background and objectives: Cardiovascular disease is a major concern in HIV-infected patients. Lifetime risk estimations use the risk of developing it over the course of remaining lifetime, and are useful in communicating this risk to young patients. We aim to describe the prevalence of cardiovascular risk factors among a representative sample of HIV-infected subjects under antiretroviral therapy in Spain, and to estimate their lifetime risk of cardiovascular disease. Methods: Cross-sectional survey about cardiovascular risk factors in 10 HIV units across Spain. Lifetime risk assessed according to Barry was classified in two major categories: low and high lifetime risk. Results: We included 895 subjects, 72% men, median age 45.7 years; median CD4 lymphocyte count 598 cells/μl, median time since HIV diagnosis 11 years, median time on antiretroviral treatment 6.3 years, 87% had undetectable HIV viral load. Tobacco smoking was the most frequent risk factor (54%), followed by dyslipidemia (48.6%) and hypertension (38.6%). Estimated 10-year coronary risk (Framingham/Regicor Risk Score) risk was low ( < 5%) in 78% of the patients, and intermediate (5–10%) in 20%. Lifetime risk estimation showed a high risk profile for 71.4% of the population studied, which was associated with increasing age, prolonged antiretroviral therapy and patient's place of origin. Conclusions: Modifiable cardiovascular risk factors in this population are very common. There are significant disparities between the low 10-year risk estimated with the Framingham/Regicor score and the higher lifetime risk in HIV patients on antiretroviral therapy. A more aggressive management of modifiable cardiovascular risk factors in these patients seems advisable.